Hyperestrogenism Affects Adult Height Outcome in Growth Hormone Treated Boys With Silver-Russell Syndrome - Kvernebo-Sunnergren, Kjersti; Ankarberg-Lindgren, Carina; Åkesson, Karin; Andersson, Mats X.; Samuelsson, Lena; Lovmar, Lovisa; Dahlgren, Jovanna (Frontiers in Endocrinology, 2018)
Background: Intrauterine growth retardation and short stature are common features in Silver-Russell syndrome (SRS). Despite recombinant growth hormone (rGH) treatment, poor pubertal height gain, affecting adult height (AH), is common. This study investigated whether growth patterns and estrogen concentrations are associated with AH outcome in rGH treated SRS males. Methods: In this retrospective longitudinal single-center study, 11 males with SRS were classified as non-responders (NR=6) or responders (R=5), depending on AH adjusted for midparental height. Epigenetic analysis and longitudinal growth measures, including bone age, rGH related parameters, pubertal development, gonadotropins and estrogen concentrations, were analyzed until AH. Results: Pubarche before 9 years was only observed in one NR. At 10 years of age, there was no difference in gonadotropins between NR and R. However, E2 concentrations at 10 years of age showed a strong association to AH adjusted for MPH (r=-0.78, p<0.001). Serum estradiol (E2) (pmol/L) was significantly higher in NR at ages 10 years (median (range) 2 (<2-5) versus <2 (<2)), 12 years (23 (10-57) versus 2 (<2-2)) and 14 years (77 (54-87) versus 24 (<2-38)) but not at 16 years. Birth weight standard deviation score (SDS) was lower in NR (-4.1 (-4.7- -2.1) versus -2.7 (- 3.3 - -1.7)). Weight gain (SDS) until pubertal onset was greater in NR (2.4 (1.4-3.5) versus 0.8 (-0.4-1.7)) and pubertal height gain (SDS) was lower in NR (-1.0 (-2.7-0.4) versus 0.1 (-0.1-1.1)). At AH, a number of NR and R had high E2 concentrations and small testis. Conclusion: Increased E2 concentrations at age 10, 12 and 14 years were associated to less pubertal height gain, thus affecting AH. Due to the small number of patients, the results need to be confirmed in larger cohorts. The finding of impaired testicular development stresses the need of hormonal evaluation as a complement to clinical and radiological assessment when predicting AH in males with SRS.